SWOT-Based Business Development Strategy for Increasing Sales Volume in Agro-Industrial MSMEs: A Case Study of Sumber Agung Farm, Bontang City - Lailatul Zulfiah Kurniasari Rahmadani; Budi Prabowo (Jurnal Investasi Islam, 2026)
This study aims to analyze the business development strategies implemented by Sumber Agung Farm MSME in increasing sales volume within a non-agrarian industrial region. Previous studies generally focused on promotional and marketing strategies, while studies discussing operational integration and customer-oriented services in supporting MSME sustainability remain limited. This study employed a qualitative descriptive approach using interviews, observation, documentation, and SWOT analysis through IFAS and EFAS matrices. The research involved ten informants consisting of one business owner, six employees, and three customers selected using purposive sampling. The findings indicate that internal raw material integration, product quality improvement, and door-to-door distribution services contributed to increasing sales volume and strengthening customer loyalty. Sales volume increased from 9,800 sacks in 2022 to 13,860 sacks in 2025. The SWOT analysis showed an IFAS score of 3.04 and an EFAS score of 3.01, indicating that the MSME was positioned in Quadrant I with strong growth opportunities through a growth-oriented strategy. This study contributes to MSME business strategy literature by emphasizing the importance of operational integration, internal resource management, and customer-oriented services in supporting business sustainability within non-agrarian industrial regions. Practically, the findings may serve as a reference for agro-industrial MSMEs in developing adaptive business strategies based on internal resource optimization and customer-oriented services.